Investigation of the relationship between care burden and anxiety levels of terminal period patient relatives - Metin Yildiz; Yakup Sarpdaği; Mehmet Salih Yildirim; Güray Okyar (National Scientific Medical Center, 2021)
Objective: This research was carried out to examine the relationship between care burden and anxiety levels of terminal period patient relatives. Material and Methods: This research, which is planned as descriptive-correlational type, was conducted between March and May 2020 in Van Training and Research Hospital. Results: According to the findings obtained from the study, the Beck Anxiety Inventory total score mean of the individuals was determined to be 16.40 ± 13.12. The total score mean of the Zarit Care Burden Scale was determined to be 50.23 ± 11.29. A positive statistically significant relationship was found between Beck Anxiety Inventory and Zarit Care Burden Scale total score means (p <0.05). Conclusion: Individuals have been found to have moderate anxiety and "severe burden". Palliative care nurses should support the psychological and basic aspects of individuals with nursing interventions necessary for caregivers to cope with anxiety and feel less care burdens. It is recommended to carry out culture-specific programs and long-term clinical studies to ensure that caregivers are able to cope with anxiety.